PENGARUH AKUNTANSI PERTANGGUNGJAWABAN DAN KUALITAS INFORMASI MANAJEMEN TERHADAP KINERJA MANAJERIAL PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA MAKASSAR: penelitian kuantitatif - nursantia ismail; Samsul Rizal; Ainun Arizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze and test the influence of Responsibility accounting and Quality of Management Information on Managerial Performance at the Regional Drinking Water Company (PDAM) of Makassar City. This study uses a quantitative approach with multiple linear regression analysis methods to test the influencw of independent variables on dependent variables. The sample used was 40 employees using the Saturated Sample Technique. The data obtained were then tested using the Statistical for the social science (SPSS) version 25 application. The results of the study showed that partial accountability accounting had a t count of 3,448 > t table 2,704 with a significance of 0,001 < a significance level of 0,005 which showed that accountability accounting had a positive effect on managerial performance in the makassar city regional drinking water company (PDAM). The quality of management information partially had a t count of 6,753 > t table 2,704 with a significance of 0,000 < 0,005 which showed that the quality of management information had a positive effect on managerial performance in the makassar city regional drinking water company (PDAM).